(untitled) (Research, Society and Development, 2023)
Managing the human resources department with a focus on the company’s strategies means being the intermediary between the departments, contributing to customer satisfaction, through the performance of better employees because they are the object of better attention by the company for working when they can do better. develop professionally, which was achieved as discussed in this article through the balance between the three dimensions to obtain the collaboration of good professionals that are to attract, retain and develop these people, attracting means making the company desired by its future collaborators, retaining is keeping developing your human capital, through motivational techniques and assessing your satisfaction, is having the ability to take care of your employees’ future by providing them with the conditions for professional improvement. When a company managed to balance these two aspects through the three dimensions, it can be said that the company is organizationally sustainable, the article also considers the employee’s commitment.